1980
DOI: 10.3109/00365518009101862
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cortisol, androstenedione, testosterone and luteinizing hormone in running exercise of different intensities

Abstract: Changes in plasma cortisol, androstenedione, testosterone and luteinizing hormone (LH) were measured in five young male sprinters after maximal short-term running and in five young male long-distance runners after moderate (90 min, 4.3 min/km) and intense (45 min, 3.3 min/km) long-term running. Short-term running increased mean plasma cortisol (27%) and androstenedione (19%) significantly; no appreciable changes were found in mean plasma testosterone or LH levels. Intense long-term running caused considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
65
2
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(87 citation statements)
references
References 18 publications
19
65
2
1
Order By: Relevance
“…In addition, no differences in final muscle glycogen levels between All the subjects felt that the fartlek run was much less exhausting than the race. This subjective feeling of fatigue after the intense run was confirmed by hormonal analyses: serum testosterone and free testosterone concentration decreased after the intense run, which is in agreement with Dessypris et al 24 and Kuoppasalmi et al 9. Increased serum cortisol values, observed in five out of six subjects after the intense run, further indicated heavy physical strain.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, no differences in final muscle glycogen levels between All the subjects felt that the fartlek run was much less exhausting than the race. This subjective feeling of fatigue after the intense run was confirmed by hormonal analyses: serum testosterone and free testosterone concentration decreased after the intense run, which is in agreement with Dessypris et al 24 and Kuoppasalmi et al 9. Increased serum cortisol values, observed in five out of six subjects after the intense run, further indicated heavy physical strain.…”
Section: Discussionsupporting
confidence: 77%
“…cortisol) hormone concentrations (Pritzlaff et al 1999, Hackney et al 2012, while prolonged and physically demanding endurance performance (e.g. a marathon run) may in its final phases lead to decreases in testosterone and simultaneous increases in cortisol concentrations (Kuoppasalmi et al 1980). …”
mentioning
confidence: 99%
“…Dulac et al found that cortisol concentrations in blood were significantly increased during long-distance swimming in cold water 98) . Serum cortisol level increases in response to exercise at moderated altitude [99][100][101] . Guilland et al observed increased urinary excretion of cortisol during mountaineering between 4,800 and 7,100 m…”
Section: Environmental Effectsmentioning
confidence: 99%